Midpoint methods for a Volterra integral equation with non-smooth solutions, “This paper has been withdrawn” - Salimi shamloo, Ali; Aliakbar Naeim, Mahtab (International Journal of Applied Mathematical Research, 2012)
This paper has been withdrawn.